Potential grizzlies : making the nonsense bearable - Welner, Kevin Grant, 1963- (Emerald Publishing Limited : Information Age Publishing, Inc., 2020)
"If all humor does indeed come from pain, then American educational policymaking has been a petri dish brimming with hilarity. Even before Betsy DeVos ascended to her perch atop the U.S. Department of Education, her predecessors had offered up an excruciating decade of fodder for satire. Ably assisted by a bevy of billionaires, foundations, and advocacy think tanks, these policymakers unleashed a torrent of rhetorical gibberish and evidence-free "innovations" on the nation's children and their schools. Potential Grizzlies: Making the Nonsense Bearable is one researcher's attempt to laugh instead of cry. The book will bring back memories of your favorite policymakers, from Michelle Rhee to Arne Duncan to Chris Christie. So sit back and relax with fond thoughts of your favorite policies, from testing to school choice to "parent trigger." Or maybe just smile and imagine a day when policymakers turn to research evidence and knowledgeable educators to build a sound future for our children"--